Carbon Footprint Implications of Demand and Supply Uncertainties in Supply Chains: A Simulation Study. (4th July 2022) - Kumar, Vikas; Das, Debadyuti; Bardhan, Amit Kumar
ABSTRACT: Supply chain uncertainties and bullwhip effect increase unproductive consumption of resources. They adversely affect the economic and environmental performance of the supply chain. The environmental implications of the bullwhip effect and uncertainties are not well researched in literature. In this paper, we study the carbon footprint implications of supply chain uncertainties through emission sources of the two most important logistical activities, i.e. warehousing and transportation. We construct a quantitative framework for calculating various performance metrics and carbon emissions of a four-tier linear supply chain. Simulation experiments were carried out to investigate how uncertainties and variations in decision inputs affect supply chain performance. Results show direct relations of uncertainties and service level, with total supply chain cost and carbon emission. The rates of change of bullwhip ratios, instead of their magnitude, can provide useful insights for handling supply chain uncertainties and improving economic and emission performance.